PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V MI MUHAMMADYAH SEI SEGAJAH KECAMATAN KUBU - Antosa, Zariul Antosa Zariul; ', Hartoyo; ', Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract : This study was conductedbecause of the low science learning outcomesof students in grade V MI Muhammadiyah Sei. From the initial tests wereperformed only 10 of 27 students who achieve KKM with an average value of59.07. The purpose of this research is to improve the learning outcomes ofstudents of class V MI IPA Muhammadiyah Sei Segajah by applying TPS learningmodel. Based on the results of the research can be seen that the activity of theteacher on the first cycle of Meeting 1 with a percentage score of 58.3%. At thesecond meeting with the increased percentage of 75% as well as in meetings withpersentae 79.16% 3 and 4 meeting with the percentage of 83.3%. In the first cycleof the first meeting of the percentage score of 58.3%. At the meeting of the firsttwo cycles the percentage of student activity score increased to 75%, in thesecond cycle which was also an increase of 79.1% in the first meeting and thesecond meeting to 83.3%. Before menggunakam cooperative learning TPS only 10students who completed the study, while 17 students did not complete. Afterlearning with cooperative learning TPS increased in the first cycle of studentswho completed as many as 13 students and 14 students did not pass well. In thesecond cycle students who completed as many as 22 students and 5 students whodid not complete classically said to be completelyKeywords : Think pair share, science learning outcomes